Leaf wax biomarkers of a high-mountain lake area in western iberia—Implications for environmental reconstructions - Santos, Ricardo N.; Schefuß, Enno; Cordeiro, Lívia Gebara M. S.; Oliveira, Dulce; Hernández, Armand; Ramos, Alexandre M.; Rodrigues, Teresa (Frontiers in Environmental Science, 2022)
Leaf wax n-alkane biomarkers are widely used to infer past vegetation dynamics and hydroclimate changes. The use of these compounds strongly relies on the characterization of modern plants. However, few studies have explored leaf waxes of modern plants and their application to reconstructing climate and environmental changes in the Iberian Peninsula, a region known for its high vulnerability to climate change. In this study, we characterize the distributions and compound-specific isotopic compositions of the leaf waxes of dominant plants in the vegetation cover, soil, and surface sediment of the Lake Peixão area, a high-mountain glacial lake in Serra da Estrela (central Portugal). Our results show that the modern oro-Mediterranean (subalpine) vegetation of the study area is dominated by C3 grasses/herbs and shrubs that preferentially produce long-chain leaf waxes (≥C27). The C31n-alkane display the overall highest concentration, produced by some grasses and shrubs, but especially Erica sp (heather), which is highlighted as a major source for the total n-alkane pool in the lake sediments. C29 is the second-most abundant and the most equally produced n-alkane of the vegetation cover; C25 and C27 homologs are mainly associated with aquatic-related grasses/herbs, while C33 and C35 are particularly linked to cold-drought tolerant Juniperus sp. shrubs. Shrubs show higher but proportional values than grasses/herbs in the isotopic space, suggesting a directly proportional physiological adaptation of the two ecological forms to the prevailing climatic and environmental factors of the study area. C29 is pointed as the most representative (or less plant-biased) leaf wax n-alkane in the lake sediments. Thus, δD of C29n-alkane is interpreted as a robust terrestrial hydrological indicator (δDterr), which signal is believed to be strongly influenced by the mean air temperature and/or precipitation amount. Despite the sparse vegetation and small catchment area, the apparent hydrogen fractionation factor, determined from δDterr of the lake surface sediment, is in line with the modeled global mean values for the latitude of the study area. The different molecular and compound-specific signatures of the studied oro-Mediterranean species have the potential to support future interpretations of leaf wax biomarkers in the Iberian Peninsula.